Non-Pharmacological Balance Therapy on Diabetic Peripheral Neuropathy Patients with Balance Disorders - Jeremy Nicolas Sibarani; Kristanti Wanito Wigati; Imam Subadi (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
ABSTRACTBackground: Patients with diabetic peripheral neuropathy (DPN) suffers from propioceptive ability and mobility disturbance which can potentially affects balance. There are various balance therapy options for DPN patients. The purpose of this study was to determine the effectiveness of various non-pharmacological therapies (surgery, traditional medicine, exercise and assistive devices) in DPN patients with balance disorders.Aim(s): To determine the effectiveness of non-pharmacological balance therapy in people with diabetic peripheral neuropathyMaterial and methods: A systematic review was conducted using randomized controlled trial study articles found using PICO characteristics in ScienceDirect and PubMed in the last 10 years. All articles were selected based on PRISMA and descriptive analysis was carried out on the selected articles.Result: Significant balance improvement found in traditional Thai massage, physical exercise therapy, assistive device therapy with whole-body vibration, and assistive device therapy with electrical stimulation. Surgical therapy with unilateral nerve decompression did not provide a significant measurable balance improvement.Conclusions: Physical exercise therapy, traditional Thai foot massage, WBV and electrical stimulation therapy (with the exception of TENS on the knee) significantly improve balance. Meanwhile, unilateral nerve decompression surgical therapy did not improve the balance significantly.